THE EFFECT OF 3N (NITENI, NIROKKE, NAMBAHI) ON ENGLISH VOCABULARY MASTERY OF ELEMENTARY SCHOOL STUDENTS - Nur Zulaifah, Ika; Azizah, Dinar Martia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
A solid vocabulary foundation is essential in learning English as a foreign language. This study examines the impact of the 3N method (Niteni, Nirokke, Nambahi), rooted in Ki Hadjar Dewantara’s educational philosophy, on English vocabulary mastery among elementary students. Using a one-group pre-test and post-test design, twelve fifth-grade students in a private English tutoring program in Yogyakarta participated in structured sessions. Vocabulary mastery was measured through four indicators: pronunciation, spelling, grammar, and meaning, based on Cameron’s framework. The 3N method was delivered in three stages: observing (Niteni), imitating (Nirokke), and creating (Nambahi), supported by comprehensible input. Results showed gains across all indicators, with the highest in meaning (gain 0.75) and spelling (gain 0.60). Behavioral improvements were also observed, including increased confidence and contextual vocabulary use. The findings indicate that the 3N method effectively enhances vocabulary skills both cognitively and behaviorally. This study provides novel empirical evidence on the integration of a culturally grounded instructional model with a linguistic measurement framework, offering a validated alternative for vocabulary instruction in early English education. ABSTRAK Penguasaan kosakata yang kuat merupakan dasar penting dalam pembelajaran Bahasa Inggris sebagai bahasa asing. Penelitian ini mengkaji pengaruh metode 3N (Niteni, Nirokke, Nambahi), yang berakar pada filosofi pendidikan Ki Hadjar Dewantara, terhadap penguasaan kosakata Bahasa Inggris siswa sekolah dasar. Dengan menggunakan desain satu kelompok pre-test dan post-test, sebanyak dua belas siswa kelas lima yang mengikuti program les privat Bahasa Inggris di Yogyakarta berpartisipasi dalam sesi pembelajaran terstruktur. Penguasaan kosakata diukur melalui empat indikator: pelafalan, ejaan, tata bahasa, dan makna, berdasarkan kerangka Cameron. Metode 3N diterapkan melalui tiga tahap: mengamati (Niteni), meniru (Nirokke), dan mencipta (Nambahi), dengan dukungan input yang dapat dipahami (comprehensible input). Hasil penelitian menunjukkan peningkatan pada semua indikator, dengan skor tertinggi pada makna (gain 0,75) dan ejaan (gain 0,60). Perubahan perilaku juga diamati, termasuk meningkatnya kepercayaan diri dan penggunaan kosakata dalam konteks. Temuan ini menunjukkan bahwa metode 3N efektif dalam meningkatkan keterampilan kosakata baik secara kognitif maupun perilaku. Penelitian ini memberikan bukti empiris baru mengenai integrasi model pembelajaran berbasis budaya lokal dengan kerangka pengukuran linguistik, sehingga menawarkan alternatif valid untuk pembelajaran kosakata pada pendidikan Bahasa Inggris anak usia dini.